2008
DOI: 10.1007/s10587-008-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

2-Normalization of lattices

Abstract: Let τ be a type of algebras. A valuation of terms of type τ is a function v assigning to each term t of type τ a value v(t) 0. For k 1, an identity s ≈ t of type τ is said to be k-normal (with respect to valuation v) if either s = t or both s and t have value k. Taking k = 1 with respect to the usual depth valuation of terms gives the well-known property of normality of identities. A variety is called k-normal (with respect to the valuation v) if all its identities are k-normal. For any variety V , there is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There are many classes of varieties which satisfy the conditions of Theorem 3.2 or Corollary 3.4. These include any variety which satisfies an idempotent identity, or even a consequence of idempotence such as x ≈ t(x) for a term t of depth at least k. As a special case, we see that the construction from [1] for 2-normalizations of lattices did not actually need the order-theoretic property of lattices, but only the idempotence of the meet and join operations. However, there are many varieties for which there is no term t fulfilling conditions (C1) and (C2).…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…There are many classes of varieties which satisfy the conditions of Theorem 3.2 or Corollary 3.4. These include any variety which satisfies an idempotent identity, or even a consequence of idempotence such as x ≈ t(x) for a term t of depth at least k. As a special case, we see that the construction from [1] for 2-normalizations of lattices did not actually need the order-theoretic property of lattices, but only the idempotence of the meet and join operations. However, there are many varieties for which there is no term t fulfilling conditions (C1) and (C2).…”
Section: Figurementioning
confidence: 97%
“…They showed that any algebra in N k (V ) is a homomorphic image of a k-choice algebra constructed from an algebra in V . In [1], Chajda, Cheng and Wismath also studied the algebras of the variety N 2 (L), the 2-normalization of the variety L of all lattices. Using the order-theoretic nature of lattices, they introduced a modification of 2-choice algebras called the 3-level inflation of an algebra, and showed that the variety N 2 (L) consists exactly of all 3-level inflations of lattices.…”
Section: Introductionmentioning
confidence: 99%